ASSESSING INSTRUCTIONAL LEADERSHIP BEHAVIORS OF THE HEADS OF SECONDARY SCHOOLS - Awan, Riffat-un-Nisa; Jabeen, Farhat; Ali, Ghazanfar (Journal of Arts & Social Sciences, 2022)
Instructional leaders are effective principals and these leaders can lead their team towards achievement of assigned targets. Instructional leadership is directly linked to supporting and helping student learning and classroom teaching. This study intends to evaluate how principals’ instructional leadership behavior make a difference in the instructional process of public secondary school, as perceived by a sample of 185 teachers of Sargodha district. A questionnaire called PIMRS (Hallinger, 1982) was adopted for collection of data. Data analysis made it clear that teachers rated their heads high on all sub scales of instructional leadership and also identified some ignored dimensions in this regard. The results revealed significant gender differences in the perception of teachers about heads’ instructional supervision, their being highly visible, encouraging teachers to develop professionally, and the heads efforts in providing incentives to students for their effective learning and better achievement. Findings also suggest that the opinion of experienced teachers about different dimensions of instructional leadership was more positive as compared to the newly inducted teachers. It was suggested that heads may be trained to be effective instructional leaders for improving students’ achievement and performance.